Alternative paths to refugee and asylum seeker protection in Malaysia and Indonesia. (June 2019) - Prabandari, Atin; Adiputera, Yunizar
This article explores how refugees in non-signatory countries in Southeast Asia, particularly Indonesia and Malaysia, have some protection through alternative paths under international refugee law. These two countries provide forms of protection even if they are not States Parties to the Refugee Convention. These two case studies show that the governance of protection for refugee and asylum seekers is provided through alternative paths, even in the absence of international law and statist processes. These alternative paths offer a degree of meaningful protection, even if this is not tantamount to resettlement. Alternative paths of protection are initiated mainly by non-state actors. The states try to manage alternative protective governance to secure their interests by maintaining their sovereignty, on the one hand, and performing humanitarian duties on the other. In this regard, Indonesia and Malaysia have resorted to meta-governance to balance these two concerns.